2020
DOI: 10.2139/ssrn.3723790
|View full text |Cite
|
Sign up to set email alerts
|

Dividend Policy and the COVID-19 Crisis

Abstract: This paper examines dividend payment behavior of the S&P1500 firms during the COVID-19 crisis characterized by the stock market crash and a V-shaped stock price recovery propelled by technology stocks. We find that the great majority of firms either maintain or increase the level of dividend payment during the crisis period. Yet, the relationship between the dividend payout and bottom-line earnings available to common shareholders is significantly negative. This relationship holds even for dividend-increasing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 34 publications
2
11
1
Order By: Relevance
“…The result deviates from the general assumption in the dividend literature that companies are generally conservative on dividend policies and may seldom cut or omit dividend payout due to the negative signal it may send to the market(Baker & Wurgler, 2016;Hardy, 2021). It also departs from a recent observation byMazur et al (2020) that most S&P 1500 firms in the US either maintain or increase dividends during the COVID-19 period. The COVID-19 pandemic has shown that managers may deviate from conservative dividend policies in highly uncertain times.The finding is consistent withNtantamis and Zhou (2022), who reported a significant dividend payment cut among G-7 countries during the COVID-19 pandemic.…”
contrasting
confidence: 91%
See 1 more Smart Citation
“…The result deviates from the general assumption in the dividend literature that companies are generally conservative on dividend policies and may seldom cut or omit dividend payout due to the negative signal it may send to the market(Baker & Wurgler, 2016;Hardy, 2021). It also departs from a recent observation byMazur et al (2020) that most S&P 1500 firms in the US either maintain or increase dividends during the COVID-19 period. The COVID-19 pandemic has shown that managers may deviate from conservative dividend policies in highly uncertain times.The finding is consistent withNtantamis and Zhou (2022), who reported a significant dividend payment cut among G-7 countries during the COVID-19 pandemic.…”
contrasting
confidence: 91%
“…Recent studies by Ali (2022) and Ntantamis and Zhou (2022) found that majority of firms listed in the G‐12 and G‐7 countries respectively cut or omitted dividends during the COVID‐19 pandemic as a way of building resilience towards the uncertainties of the crises. An exception, however, is a study by Mazur et al (2020) who reported that most S&P 1500 firms in the US either maintained or increased dividends during the COVID‐19 period. Considering the impact of the pandemic on South Africa and its economy we posit a negative impact of the pandemic on dividend payout.…”
Section: Theoretical Framework and Development Of Hypothesismentioning
confidence: 99%
“…Several studies focus on the effect of Covid-19 on financial markets, such as the impact on stock market returns and volatility (Al-Awadhi et al, 2020;Albulescu, 2020;Ali et al, 2020;Ashraf, 2020bAshraf, , 2020cBahrini & Filfilan, 2020;Contessi & Pierangelo, 2020;Gu et al, 2020;Harjoto et al, 2020;Kartal, Kılıç-Depren, & Depren, 2020;Mazur, Dang, & Vega, 2020;Rababah et al, 2020;Sergi et al, 2021;Thorbecke, 2020;Topcu & Gulal, 2020), trade volume (Chiah & Zhong, 2020;Harjoto et al, 2020), stock repurchases (Pirgaip, 2021), government responses or interventions (Ashraf, 2020a;Chen et al, 2020;Zaremba et al, 2020;Zaremba et al, 2021), contagion effect (Okorie & Lin, 2020), market illiquidity (Baig et al, 2020), tourism and leisure sectors (Karabulut et al, 2020;Ghosh, 2020;Kaczmarek et al, 2021), herding behavior (Chang, McAleer, & Wang, 2020;Espinosa-Méndez & Arias, 2020), cryptocurrencies (Conlon & McGee, 2020Corbet, Larkin, & Lucey, 2020;, mutual funds (Mirza et al, 2020;Yarovaya et al, 2021), dividends (Krieger, Mauck, & Pruitt, 2020;Mazur, Dang, & Vo, 2020), uncertainty (Jeris & Nath, 2020), housing prices (Qian, Qiu, & Zhang, 2021) and oil prices (Corbe...…”
Section: Introductionmentioning
confidence: 99%
“…An important aspect of the companies' financial policy is the dividend payment policy. Examining the dividend policy of the companies included in the S&P1500 index basket, Mazur et al (2020) conclude that over 80% of the observed companies maintained or even increased the number of dividends paid, regardless of the deterioration caused by the pandemic. On the other hand, Pettenuzzo et al (2021) observed a significantly larger sample of American companies 1 , and found a significantly larger sample of American companies that withdrew from the payment of dividends and strengthened their cash positions, often seeking external sources of financing.…”
Section: Literature Reviewmentioning
confidence: 96%